2009
DOI: 10.1111/j.1442-9071.2008.01910.x
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba keratitis cluster: an increase in Acanthamoeba keratitis in Australia

Abstract: There has been a significant increase in incidence of cases of Acanthamoeba keratitis presenting to our institution. The type of contact lens solution and the use of silicon hydrogel lenses combined with extended overnight wear may play a role; however, the significance is unclear given the small numbers for analysis. Further study of incidence and patient characteristics is warranted to identify risk factors and causes for the rising incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 54 publications
1
21
0
1
Order By: Relevance
“…A similar trend has been noted internationally in centres such as Chicago, USA 15 . A sixfold increase in the incidence of AK presenting to Princess Alexandra hospital, Queensland was also recently reported 16 . Although AMO Complete MoisturePlus Multi‐Purpose Solution use has been demonstrated to be independently associated with AK among soft contact lens users, it does not explain all cases in the recent outbreaks, suggesting that there are additional risk factors 8 .…”
Section: Discussionsupporting
confidence: 64%
“…A similar trend has been noted internationally in centres such as Chicago, USA 15 . A sixfold increase in the incidence of AK presenting to Princess Alexandra hospital, Queensland was also recently reported 16 . Although AMO Complete MoisturePlus Multi‐Purpose Solution use has been demonstrated to be independently associated with AK among soft contact lens users, it does not explain all cases in the recent outbreaks, suggesting that there are additional risk factors 8 .…”
Section: Discussionsupporting
confidence: 64%
“…Acanthamoeba keratitis (AK) is a serious infection that can result in permanent visual impairment or blindness. Several factors are involved in increasing its visual morbidity including the aggressive nature of the parasite, difficulties in diagnosis and reduced immune status of the host [4][5][6][7]. Due to the overall difficulty in diagnosing and treating AK, much effort of late has focused on prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The wide range in incidence (1.5 per year9 to 31 cases per year10) is thought to be due to the variability in type and frequency of CL use, contamination of domestic and swimming pool water, the amoebicidal efficacy of CL cleaning solutions and availability of diagnostic techniques for AK 2 6. There has been a paucity of Australian studies with the most recent one published in 2009, where 13 patients in Brisbane, Queensland, were identified over a 4-year period (2003–2007) 11. Another study reported 20 patients treated at the Sydney Eye Hospital, New South Wales, over a 6-year period from 1997 to 2002 12…”
Section: Introductionmentioning
confidence: 99%